Hemorrhoidectomy versus rubber band ligation in treatment of second and third degree hemorrhoids: a comparative study - Thakkar, Nimesh B. (International Journal of Research in Medical Sciences, 2019)
Background: Optimum surgical intervention for low-grade haemorrhoids is unknown. Haemorrhoidal artery ligation (HAL) has been proposed as an efficacious, safe therapy while rubber band ligation (RBL) is a commonly used Out patient treatment. Methods: We compared recurrence after HAL versus RBL in patients with grade II-III haemorrhoids. The diagnosis of hemorrhoids is primarily based on the proctoscopic examination. The study evaluates comparative results of rubber band ligation (RBL) and hemorrhoidectomy. This study was conducted over a period of 1 year from January 2017 to December 2017. It includes 50 patients having second- or third-degree primary hemorrhoids who attended surgical OPD of Tertiary Care Hospital in Gujarat. These 50 patients were selected randomly and divided into two groups of 25 patients each (hemorrhoidectomy group and RBL group). Patients of fissure, fistulae, and malignancy were excluded. All parameters were recorded and finally analysed. Results: Hemorrhoidectomy and RBL are equally effective especially in second-degree hemorrhoids. However, RBL should be considered the first-line treatment in second-degree hemorrhoids because being an outpatient procedure, it is cost effective for the patients, saves many hospital beds for more sick patients, and takes the pressure off the surgical waiting list. Although RBL is not as effective as hemorrhoidectomy in third-degree hemorrhoid, it does improve bleeding and prolapse and is highly recommended for patients who are unfit for surgery. Conclusions: RBL should be considered as the first-line treatment for second-degree hemorrhoid. However, in the third-degree hemorrhoids, hemorrhoidectomy achieves better results, and RBL is recommend as the first-line treatment for those patients in whom there is contraindication for surgery or anesthesia.